Internet and Mental Health of Adolescents - Opsenica Kostić, Jelena J.; Panić, Tanja P. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Today’s generations of adolescents have grown up with information and communication technologies which have a significant place in their lives. One of the important issues in this context is the relation between the Internet and the mental health of adolescents. The first topic that this paper deals with, is the relationship between the use of the Internet and mental health, and the other is related to the planned use of the Internet for the purpose of improving wellbeing. The most common activity of young people on the Internet is social networking. Online social networks can positively affect wellbeing through facilitating self-disclosing and the availability of social support. Such findings from empirical research support the ideas of theories that emphasize the positive aspects of online relating. However, social networks (and online communication in general) can also have significant negative effects on the mental health of adolescents, if they are exposed to cyberbullying. The second topic of the paper is the planned use of the Internet for the purpose of improving mental health. To young people (and to members of other age groups, as well) online support groups are the most accessible nowadays, aimed at supporting a group of people with a common problem or life challenge. These forums are most often text-based and this kind of communication has a number of potential benefits for users. It is also possible to organize online interventions that promote mental health and prevent its deterioration. Research shows that online skill-based interventions can have a positive impact on adolescent mental health. The results of the online prevention interventions indicate the encouraging evidence concerning computerized cognitive behavioral therapy interventions and their impact on adolescent’s anxiety and depression symptoms. Although it contains potentially negative aspects, the Internet has a positive significance and potential for the development of adolescents.